Synthesis And Characterization Of Sb2O3 Nanoparticles By Chemical Reduction Method - Chin , Hui Shun (2012)
Antimony trioxide (Sb2O3) nanoparticles with particle size less than 100 nm, spherical in shape and well distributed were successfully synthesized by chemical reducing method. Antimony trichloride (SbCl3) was reduced by hydrazine in the presence of sodium hydroxide (NaOH) as catalyst in ethylene glycol (EG) at 120 oC for 60 minutes. In order to synthesis Sb2O3 nanoparticles with smaller particle size (2 - 12 nm), spherical in shape and well distribution, effects of hydrazine concentration ([N2H5OH]/[SbCl3] = 0.75, 5, 10, 20 and 30), NaOH concentration ([NaOH]/[SbCl3] = 0, 1, 3 and 5), precursor concentration ([SbCl3]/[N2H5OH] = 0.05, 0.1, 0.15 and 0.2), reaction temperature (60, 90, 120 and 150oC), reaction time (30, 60, 90 and 120 minutes) and boiling temperature (25, 50, 80 and 110oC) were investigated.